2015
DOI: 10.1155/2015/283576
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Drainage of Pelvic Abscesses and Collections Using Transabdominal Ultrasound Guidance

Abstract: Objectives. To evaluate clinical outcomes following transvaginal catheter placement using transabdominal ultrasound guidance for management of pelvic fluid collections. Methods. A retrospective review was performed for all patients who underwent transvaginal catheter drainage of pelvic fluid collections utilizing transabdominal ultrasound guidance between July 2008 and July 2013. 24 consecutive patients were identified and 24 catheters were placed. Results. The mean age of patients was 48.1 years (range = 27–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…After the onset of symptoms and a CT scan, a vaginal ultrasound revealed the underlying abscess, which required drainage. The standard management of a pelvic abscess requires a minimally invasive technique, such as non-surgical percutaneous drainage, laparoscopic surgery, or transvaginal catheter placement (8). Because she had a hysterectomy and the abscess was located at the vaginal cuff, we decided to re-open one of the stitches and drain the fluid through the opening.…”
Section: Discussionmentioning
confidence: 99%
“…After the onset of symptoms and a CT scan, a vaginal ultrasound revealed the underlying abscess, which required drainage. The standard management of a pelvic abscess requires a minimally invasive technique, such as non-surgical percutaneous drainage, laparoscopic surgery, or transvaginal catheter placement (8). Because she had a hysterectomy and the abscess was located at the vaginal cuff, we decided to re-open one of the stitches and drain the fluid through the opening.…”
Section: Discussionmentioning
confidence: 99%
“…Transrectal or transvaginal drainage of the pelvic collection can be a promising option to overcome these difficulties. Transvaginal drainage of pelvic collections clinical success rate may reach up to 100% [8] , but these methods are often under-used where expertise in techniques is limited. The availability of radiologists familiar with the technique, concern about the effectiveness, and long-term complication is likely to be reasons for the limited use of these procedures [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Other minimally invasive procedures used in treatment of gynecological conditions are using transabdominal or transvaginal ultrasound drainage of pelvic abscess. In the study of Ching and Sumkin, they found 100% clinical success using this procedure for drainage of pelvic abscess [15].…”
Section: Introductionmentioning
confidence: 99%